Comparative Analysis of Complete Chloroplast Genomes of Anemoclema, Anemone, Pulsatilla, and Hepatica Revealing Structural Variations Among Genera in Tribe Anemoneae (Ranunculaceae) - Liu, Huijie; He, Jian; Ding, Chuanhua; Lyu, Rudan; Pei, Linying; Cheng, Jin; Xie, Lei (Frontiers in Plant Science, 2018)
Structural rearrangements of Anemone species’ chloroplast genome has been reported based on genetic mapping of restriction sites but has never been confirmed by genomic studies. We used a next-generation sequencing method to characterize the complete chloroplast genomes of five species in the tribe Anemoneae. Plastid genomes were assembled using de novo assembling methods combined with conventional Sanger sequencing to fill the gaps. The gene order of the chloroplast genomes of tribe Anemoneae was compared with that of other Ranunculaceae species. Multiple inversions and transpositions were detected in tribe Anemoneae. Anemoclema, Anemone, Hepatica and Pulsatilla shared the same gene order, which contained three inversions in the large single copy region (LSC) compared to other Ranunculaceae genera. Archiclematis, Clematis, and Naravelia shared the same gene order containing two inversions and one transposition in LSC. A roughly 4.4 kb expansion region in inverted repeat (IR) regions was detected in tribe Anemoneae, suggesting that this expansion event may be a synapomorphy for this group. Plastome phylogenomic analyses using parsimony and a Bayesian method with implementation of partitioned models generated a well resolved phylogeny of Ranunculaceae. These results suggest that evaluation of chloroplast genomes may result in improved resolution of family phylogenies. Samples of Anemone, Hepatica, and Pulsatilla were tested to form paraphyletic grades within tribe Anemoneae. Anemoclema was a sister clade to Clematis. Structual variation of the plastid genome within tribe Anemoneae provided strong phylogenetic information for Ranunculaceae.